2020
DOI: 10.3897/phytokeys.138.36144
|View full text |Cite
|
Sign up to set email alerts
|

An annotated checklist of Myanmar orchid flora

Abstract: Myanmar is situated in Southeast Asia, where species richness and diversity are very high. Myanmar orchid flora is very rich, but still poorly known because botanical explorations have sharply decreased in Myanmar since 1950. The present study provides a checklist of Myanmar orchid flora which includes 1040 species and 151 genera currently known from Myanmar, based on the herbarium specimens, literature and online databases. The number of species is increased by approximately 200 species more than that given i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…These new taxa and records are mainly distributed in southeast Xizang, the Hengduan Mountains and southeast Yunnan, which are regarded as hotspots of orchid diversity as well as hotspots for China's endemic flora in general ( Zhang et al., 2015 ; Huang et al., 2016 ). The majority of our knowledge of orchids from these regions is accumulated from floras ( Chen et al., 2009 ; Xu et al., 2010 ; Jin et al., 2019 ), ongoing regional surveys ( Jin et al., 2018 ; Wang et al., 2018 ) and descriptions of new species ( Hu et al., 2013 ; Averyanov et al., 2015 , 2019 ; Liu et al., 2016a ; Zhai et al., 2017 ; Zhang et al., 2017 ; Cai et al., 2019 ; Li et al., 2019 ; Ya et al., 2019a , b ; Aung et al., 2020 ; Du et al., 2020 ; Yang et al., 2020 ). The geographic distributions of many species remain unknown, and the potential discovery of undescribed orchid species, especially in the shrinking primeval forests of the region, requires continued field work.…”
Section: Discussionmentioning
confidence: 99%
“…These new taxa and records are mainly distributed in southeast Xizang, the Hengduan Mountains and southeast Yunnan, which are regarded as hotspots of orchid diversity as well as hotspots for China's endemic flora in general ( Zhang et al., 2015 ; Huang et al., 2016 ). The majority of our knowledge of orchids from these regions is accumulated from floras ( Chen et al., 2009 ; Xu et al., 2010 ; Jin et al., 2019 ), ongoing regional surveys ( Jin et al., 2018 ; Wang et al., 2018 ) and descriptions of new species ( Hu et al., 2013 ; Averyanov et al., 2015 , 2019 ; Liu et al., 2016a ; Zhai et al., 2017 ; Zhang et al., 2017 ; Cai et al., 2019 ; Li et al., 2019 ; Ya et al., 2019a , b ; Aung et al., 2020 ; Du et al., 2020 ; Yang et al., 2020 ). The geographic distributions of many species remain unknown, and the potential discovery of undescribed orchid species, especially in the shrinking primeval forests of the region, requires continued field work.…”
Section: Discussionmentioning
confidence: 99%
“…That genus has been widely demonstrated to be paraphyletic (Cameron 2005;Pridgeon et al 2005;Tsutsumi et al 2007;Li et al 2013Li et al , 2020Su et al 2015;Tang et al 2015;Kumar et al 2022). Cameron (2005) Margońska & Szlachetko 2001Margońska 2006;Li et al 2020), though some authors still advocate for broad concepts of varying circumscription (Smith 1909;Blaxell 1978;Gray 1992;Seidenfaden 1992;Comber 2001;Schuiteman et al 2001Schuiteman et al -2010Jones & Clements 2004Jones 2006Jones , 2021Jones et al 2006Jones et al , 2010Bostock 2008;Chen et al 2009;Li & Yan 2013;Zhou et al 2016;Li et al 2019;Aung et al 2020;Gray et al 2021). Su et al (2015), in a more detailed study based on analysis of 74 species of Malaxideae that included material of Empusa habenarina, reaffirmed the earlier work of Cameron (2005, demonstrating the paraphyly of Liparis s. lat.. Studies by Su et al (2015) and Kumar et al (2022) also revealed that E. habenarina does not align with Liparis sens.…”
Section: Notesmentioning
confidence: 99%
“…The presence and distribution of species of this family have been assessed at different scales as most of them are rare, threatened or endangered (Cribb et al 2003). A checklist is a "card collection" aiming at listing all the taxa belonging to the studied taxonomic group and reporting whether they are observed, collected or reported in literature for a given area (e.g., Mathew & George 2015;Aung et al 2020;Popovich et al 2020). The taxa are typically identified at species or subspecies level, some sites of growth are reported together with other information on the habitats, variety, rarity, ecology, chorology, systematic or taxonomic issues.…”
Section: Introductionmentioning
confidence: 99%